2012
DOI: 10.1080/02791072.2012.684621
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain and Addiction: Challenging Co-occurring Disorders

Abstract: Chronic pain is commonly treated by prescribing an opioid medication. For those suffering from both chronic pain and substance dependence, barriers to adequate pain management increase. This often causes both disorders to exacerbate one another. Effective treatment may also be hampered by opioid-induced hyperalgesia, tolerance, physical dependence, "chemical coping," and diminished physical and emotional functioning. This article reviews current research trends, potential problems stemming from prescription op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 36 publications
0
21
0
1
Order By: Relevance
“…Increases in CBR expression result in increased potency or efficacy of the exogenously applied CBs 9 and may also account for the effectiveness of CBs in alleviating neuropathic pain symptoms after chronic repeated treatment, 10 unlike opioids, which have only limited long-term effectiveness. 11 While selective activation of CB2Rs also inhibits experimentally induced inflammatory pain and itch or the persistent pain of neuropathic origin, 10b,12 activation of both CB1R and CB2Rs appears to have synergistic effects on pain suppression. 12a These studies provided a rationale for the development of peripherally acting endocannabinoid-based therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in CBR expression result in increased potency or efficacy of the exogenously applied CBs 9 and may also account for the effectiveness of CBs in alleviating neuropathic pain symptoms after chronic repeated treatment, 10 unlike opioids, which have only limited long-term effectiveness. 11 While selective activation of CB2Rs also inhibits experimentally induced inflammatory pain and itch or the persistent pain of neuropathic origin, 10b,12 activation of both CB1R and CB2Rs appears to have synergistic effects on pain suppression. 12a These studies provided a rationale for the development of peripherally acting endocannabinoid-based therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Men, adults with Axis I and Axis II DSM-IV diagnoses, respondents residing in the West, and young or middle aged adults were at greatest risk for prescription drug misuse and a prescription opioid use disorder. Other studies have identified a history of alcohol or illicit drug misuse, anxiety, depression, and chronic pain as significant risk factors for prescription opioid misuse and dependence (Amari, Rehm, Goldner, & Fischer, 2011; Pohl & Smith, 2012; Turk, Swanson, & Gatchel, 2008). Individuals suffering from chronic pain disorders, who are at risk for becoming physically dependent on opioid analgesics when adhering to their prescribed medication regimen, may be particularly vulnerable to prescription opioid misuse (Butler et al, 2007; Ives et al, 2006; Sullivan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, some have used the terms chemical copers, aberrant behavior, and substance abusers interchangeably, while others have considered chemical coping as a distinct entity along the spectrum of opioid misuse in the chronic pain and cancer pain settings. [3][4][5] More recently, Del Fabbro defined chemical coping as the use of variable amounts of ''opioid analgesics to cope with their psychological or spiritual distress. '' 6 Although ''chemical coping'' is used by clinicians and investigators, the lack of definitional clarity poses a barrier to effective clinical care, education, and research.…”
mentioning
confidence: 99%